Recovery of stepping and coordination in dogs following acute thoracolumbar intervertebral disc herniations. (July 2016) - Rousse, C.A.; Olby, N.J.; Williams, K.; Harris, T.L.; Griffith, E.H.; Mariani, C.L.; Muñana, K.R.; Early, P.J.
Highlights: We examined the recovery of 62 dogs with acute thoracolumbar disc herniations. Stepping and coordination scores and an ordinal gait scale were used. Recovery of stepping was rapid and excellent in dogs with incomplete injuries. Recovery of coordination was incomplete, even with good recovery of stepping. Dogs with complete injuries segregated into dogs that did or did not recover stepping. Abstract: Prospective data on the recovery of coordination in dogs suffering acute thoracolumbar intervertebral disc herniations (TL-IVDH) are limited. The purpose of this study was to use treadmill based and open field scores (OFS) to quantify recovery of stepping ability and forelimb, hindlimb coordination in the 6 weeks following surgical decompression of dogs with TL-IVDH. Sixty-three dogs were grouped at presentation as grades 3 (non-ambulatory paraparetic), 4 (paraplegic) or 5 (paraplegic without pain sensation) and were evaluated 2, 4, and 6 weeks post-operatively. Stepping scores and Regularity Index (RI), a measure of coordination, were calculated from treadmill walking, and an OFS incorporating supported and unsupported walking was assigned. Outcomes for the three measures were compared between groups and correlation between scoring methods was assessed. Grade 3 and 4 dogs recovered ambulation by 2 weeks, reaching median stepping scores of 96 and 90% by 6 weeks, respectively. Recovery of coordination differed between groups 3 and 4 with median RI scores of 93.9% and 63%, respectively, by 6 weeks. Eight grade 5 dogs failed to recover independent ambulation by 6 weeks. Nine dogs recovered with scores that were significantly worse than the grade 3 and 4 dogs at 6 weeks for stepping score ( P < 0.001) and RI ( P < 0.001). OFS correlated closely with stepping and RI scores and each group was significantly different using this ordinal scale. In conclusion, recovery of coordination was incomplete in dogs that showed good recovery of stepping. The data generated could be used for clinical trial design.